2019
DOI: 10.3390/w11081586
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of Groundwater Recharge Zones in a Rural and Semi-Arid Region for Sustainable Water Management: Case Study in Guadalupe Valley, Mexico

Abstract: Around the world, groundwater constitutes approximately 94% of the total volume of freshwater, providing a wide range of economic and environmental services. In Baja California, Mexico, groundwater provides around 60% of the required demand and has become an essential source for agriculture, industry and domestic use. Particularly, in the Guadalupe Valley, in the municipality of Ensenada, the development of diverse activities depends on the water stored in the aquifer. Among these activities, agroindustry stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Water is the limiting factor for ecological attributes in arid and semiarid areas, and vegetation dynamics are highly sensitive to alterations in water availability. This indicates that water conveyance is necessary for protecting important vulnerable ecological regions (Alejandro Saiz-Rodriguez et al, 2019). Peterman et al (2014) showed that annual was very sensitive to soil depth in simulations of carbon and hydrological variables.…”
Section: The Effects Of Climate Change On Ndvimentioning
confidence: 96%
“…Water is the limiting factor for ecological attributes in arid and semiarid areas, and vegetation dynamics are highly sensitive to alterations in water availability. This indicates that water conveyance is necessary for protecting important vulnerable ecological regions (Alejandro Saiz-Rodriguez et al, 2019). Peterman et al (2014) showed that annual was very sensitive to soil depth in simulations of carbon and hydrological variables.…”
Section: The Effects Of Climate Change On Ndvimentioning
confidence: 96%
“…Land use in GV is mainly agricultural [40]. Vine and olive crops are the most representative and suitable for development in the semi-arid Mediterranean climate of the region [47]. Geologically, the GA is an unconfined heterogeneous aquifer formed by two tectonic grabens, which resulted from normal faults, filled by unconsolidated Quaternary sediments (gravels, sands, clay lenses, and silts) [43].…”
Section: Study Areamentioning
confidence: 99%
“…Land use in GV is mainly agricultural [40]. Vine and olive crops are the most representative and suitable for development in the semi-arid Mediterranean climate of the region [47].…”
Section: Study Areamentioning
confidence: 99%
“…Therefore, it is necessary to carry out actions that allow this situation to be controlled and reversed. For example, Saíz-Rodríguez et al [69] conducted a study to identify possible locations of artificial recharging of the aquifers in the Valley of Guadalupe (Baja Califormia) while González-Trinidad et al [70] did the same for the State of Zacatecas. On the other hand, with respect to agricultural activity, incorporating conservation practices and increasing the organic material of the soil can favour the infiltration of rainwater and increase the productivity of the soil, reducing the water needs of the crops [71].…”
Section: Abstract Analysismentioning
confidence: 99%